A review of wireless access vehicular environment multichannel operational medium access control protocols: Quality-of-service analysis and other related issues - Illa Ul Rasool; Yousaf Bin Zikria; Sung Won Kim (International Journal of Distributed Sensor Networks)
In recent years, the increase in vehicular traffic has led to a drastic increase in road accidents, thus requiring adequate vehicle safety measures. The intelligent transportation system is a branch of modern technology responsible for delivering such road safety services. The wireless access vehicular environment standard defines how these intelligent transportation system applications can be incorporated in highly varying vehicular ad hoc network environments. Wireless access vehicular environment comprises the IEEE 802.11p and IEEE 1609.4 standards responsible for handling medium access control and transmission mechanisms in vehicular ad hoc networks. However, these standards still face medium access control and physical layer challenges, which must be addressed for reliable quality of service. Several research studies have been proposed and are still underway into improving medium access control protocols in the wireless access vehicular environment stack model defined by IEEE 1609.4 multichannel operation. These proposed medium access control protocols refine the quality of service and reliability of certain performance parameters and have also added some limitations. The working of such wireless access vehicular environment medium access control protocols can be enhanced by defining their limitations and improving them, without causing any performance tradeoffs. Finally, this article works toward reviewing and analyzing such limitations and tradeoffs to provide insight into possible improvements for future medium access control research deployments.